Research on deformation features and control strategies of repeated mining roadways in Guanjiaya Coal Mine - ZHAO Jie; ZHANG Ningbo; LIU Haibing (Gong-kuang zidonghua, 2024)
The surrounding rock of the repeated mining roadway is severely deformed and cannot be reused, and the repeated mining roadway has obvious overlapping extension features during the service period. In order to solve the above problems, this study takes the 13092 roadway of Guanjiaya Coal Mine as the research background, and adopts on-site measurement, numerical simulation, and theoretical analysis methods to investigate the overlapping extension features and control measures of repeated mining roadway deformation. The analysis of deformation features of repeated mining roadways shows the following points. ① Under a single mining disturbance, the deformation of repeated mining roadways exhibits zoning and asymmetric failure features, which can be divided into rapid deformation zone, strong deformation zone, and slow deformation zone. The crack damage mainly occurs in the coal wall and coal pillar walls, with less damage to the roof and floor, manifested as significant fragmentation and inward movement of the two sides of the roadway. Severe deformation occurs at the intersection of the coal wall and roof, as well as the coal pillar and floor. ② The secondary mining roadway expands and overlaps on the basis of the primary damage, making the asymmetric damage more significant and forming a butterfly shaped plastic failure zone in the surrounding rock of the roadway. ③ The key time for controlling the surrounding rock of the repeated mining roadway is the first mining stage. The key area is the coal pillar side of the roadway in the strong deformation zone and the slow deformation zone. By analyzing the butterfly deformation features and failure zoning rules of mining roadways, a multi-level coupling control technology for repeated mining roadways is proposed. Shallow low pressure - deep high pressure grouting is used to improve the support force of coal pillars. The anchor cables are used to reinforce and improve the support force of support bodies, achieving coupling control. The comparative analysis of deformation before and after reinforcement has verified that multi-level coupling control meets the requirements of roadway reuse.